PEMALSUAN IDENTITAS SEBAGAI ALASAN PEMBATALAN PERKAWINAN DAN AKIBAT HUKUMNYA TERHADAP HAK ASUH ANAK SERTA HARTA PERKAWINAN - Calysta Dwiayu Wisnu Putri (2023)
Marriage is an inner and outer bond between a man and a woman as husband and wife with the aim of forming an eternally happy family based on the one and only God, there are conditions that are set if you want to get married. If these conditions are not met, then the marriage can be annulled, one of the reasons is identity falsification in the form of personal documents with the cancellation of the marriage there will be legal consequences for child custody and also the marital assets of the marriage. The research method used in this research is normative juridical research. Normative research is research that examines document studies, namely using various secondary data such as laws and regulations, legal theory and in the form of opinions of scholars. This normative research is focused on examining the application of the rules or norms in the applicable positive law. The data source in this study uses secondary data sources consisting of primary legal materials. Based on this research, marriage annulment can have an impact on child custody, the status of children born in an annulled marriage can become unclear and also in cases of marriage annulment due to falsification of identity, the distribution of marital assets depends on the applicable laws and regulations. The court also considers financial contributions and non-financially during the marriage, and if either spouse makes a significant contribution, the court may award compensation.